THE TRADITIONAL ELA: THE URARINA´S TRADITIONAL USE OF PLANT SPECIES FROM WETLANDS FOR WEAVING IN THE CHAMBIRA RIVER WATERSHED, LORETO, PERU - MARTÍN BRAÑAS, Manuel (2020)
In the Chambira River Watershed, Loreto, Peru. Uranina women are well known for weaving mats called ela or cachihuango from aguaje palm (Mauritia flexuosa) fiber and other wetland plant species. The ela fabric becomes a sign of identity that unites past and present generations, through the link made between the elder master weaver and the young apprentice. The objectives of this study were to explore the plant species used by two urarinas communities in the production of mats. We conducted semi-structured interviews, observed textile practice, and visited areas where plant species were collected. We identified seven plant species that were used directly or indirectly in the production of ela. The findings reinforce the idea of the late adaptation of the Urarina people to wetlands and the potential role that traditional practice has for its conservation.